2016
DOI: 10.1002/ptr.5746
|View full text |Cite
|
Sign up to set email alerts
|

Withanolides against TLR4‐Activated Innate Inflammatory Signalling Pathways: A Comparative Computational and Experimental Study

Abstract: Innate inflammations are dominant causes of poor health and high mortality. The pathogen-associated molecular pattern and lipopolysaccharide (LPS) are sensed by immune cells through activation of toll-like receptor 4 leading to mitogen-activated protein kinases (MAPKs) and NF-κB activations. Controlled MAPK and Nf-κB inhibitors have been proposed as potential antiinflammatory drugs. Withania somnifera is an important medicinal herb with known antiinflammatory activity. In this study, the selected Withania somn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Additionally, the unstimulated macrophages generally display spear and smooth shaped forms. Upon exposing to various inflammatory stimuli, such as LPS, the macrophages display an activated phenotype, which mainly manifested as irregular and rough form with accelerated spreading and pseudopodia-like formations (Purushotham et al 2017). As expected, LPS caused irregular and rough form with accelerated spreading in RAW264.7 cells, which can be obviously improved by ajudecumin A treatment (Figure 1(C)).…”
Section: Resultssupporting
confidence: 67%
“…Additionally, the unstimulated macrophages generally display spear and smooth shaped forms. Upon exposing to various inflammatory stimuli, such as LPS, the macrophages display an activated phenotype, which mainly manifested as irregular and rough form with accelerated spreading and pseudopodia-like formations (Purushotham et al 2017). As expected, LPS caused irregular and rough form with accelerated spreading in RAW264.7 cells, which can be obviously improved by ajudecumin A treatment (Figure 1(C)).…”
Section: Resultssupporting
confidence: 67%
“…WA suppressed Helicobacter Pylori induced NFkB activation and downstream signaling pathways in bone marrow derived dendritic cells and macrophages 48 . WA inhibited NFkB nuclear translocation in LPS induced bone marrow-derived macrophages 49 . In T and B lymphocytes, WA inhibited NFkB nuclear translocation, proliferation and secretion of Th1 and Th2 cytokines 26 .…”
Section: Discussionmentioning
confidence: 92%
“…It was shown to cause selective cytotoxicity on cancer cells by irreversibly damaging DNA repair mechanisms, disturbing the cellular assembly and organization, and mortalin-p53 function [18,19,24]. Several studies have suggested anti-inflammatory and anti-stress potential of Wi-N [38,39]; they have attributed this property to the oxidized 5-7 carbons in its chemistry [40] that translates into weak binding affinity to target proteins [19]. In the normal cells, it delayed the onset of stress-induced senescence [27], and protected brain-derived cells from oxidative and glutamate stresses [22].…”
Section: Discussionmentioning
confidence: 99%